Illuminations in the Manuscripts of Alain Chartier - Serchuk, Camille (A companion to Alain Chartier (c. 1385-1430): father of French eloquence, 2015)
In Alain Chartier: Père de l'éloquence française contributors explore the diverse literary production of this influential late-medieval writer, whose concern with personal and political ethics and renovation of poetic form inspired generations of writers, and still resonate with modern readers.
Keywords: Chartier; Alain; active 15th century; Criticism and interpretation; Eloquence in literature; European; French; French literature; Histoire et critique; History and criticism; Jusqu'à 1500; LITERARY CRITICISM; Literature; Medieval; Littérature française; Littérature médiévale; To 1500; dept.art; Éloquence dans la littérature